2021
DOI: 10.1002/sctm.20-0497
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Diabetic Foot Ulcers with Adipose-Derived Stromal Vascular Fraction Cell Injections: Safety and Evidence of Efficacy at 1 Year

Abstract: Diabetes affects multiple systems in complex manners. Diabetic foot ulcers (DFUs) are a result of diabetes-induced microarterial vessel disease and peripheral neuropathy. The presence of arteriosclerosis-induced macroarterial disease can further complicate DFU pathophysiology. Recent studies suggest that mesenchymal stromal cell therapies can enhance tissue regeneration. This phase I study was designed to determine the safety and explore the efficacy of local injections of autologous adiposederived stromal vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…The therapeutic potential of MSCs has been widely demonstrated in various diseases, including asthma ( 16), rheumatoid arthritis (17,18), and Crohn's disease (19,20). Numerous clinical trials and tests around the world have validated the ability of MSCs to alleviate inflammation (15,21,22). In this study, we demonstrated that MSC and MSC-GFP can reverse LPS-induced injury in EpH4-Ev cells.…”
Section: Discussionmentioning
confidence: 60%
“…The therapeutic potential of MSCs has been widely demonstrated in various diseases, including asthma ( 16), rheumatoid arthritis (17,18), and Crohn's disease (19,20). Numerous clinical trials and tests around the world have validated the ability of MSCs to alleviate inflammation (15,21,22). In this study, we demonstrated that MSC and MSC-GFP can reverse LPS-induced injury in EpH4-Ev cells.…”
Section: Discussionmentioning
confidence: 60%
“…Although the treatment consisted of simultaneous systemic and local injection therapy combined with topical application [ 18 ]. Other studies have examined the safety of topically applied adipose tissue derived MSCs and did not report any AEs associated to the investigated treatment [ 28 , 29 ]. However, no studies have reported on safety or efficacy when treating DFUs with topical BM-MSCs alone.…”
Section: Discussionmentioning
confidence: 99%
“…AT-MSCs and their secretome are described not only in in vitro studies, but also in many clinical trials. A recent publication by Carstens et al [ 94 ] demonstrated the safety and beneficial effect of an adipose stromal vascular fraction injection, containing both endothelial progenitor cells and MSCs, into the wound bed and periphery of patients with large diabetic foot ulcers (>3 cm in diameter). Over a one-year observation, significant wound healing was observed, leading to complete healing of the wound in the majority of cases.…”
Section: At-mscs and Their Derivatives: Contribution To Regenerative ...mentioning
confidence: 99%